Long Social Distancing - Barrero, Jose Maria; Bloom, Nicholas; Davis, Steven J. (Journal of Labor Economics, 2023)
Many Americans continued some forms of social distancing after the pandemic. This phenomenon is stronger among older persons, less educated individuals, and those who interact daily with persons at high risk from infectious diseases. Regression models fit to individual-level data suggest that social distancing lowered labor force participation by 2.4 percentage points in 2022, 1.2 points on an earnings-weighted basis. When combined with simple equilibrium models, our results imply that the social distancing drag on participation reduced US output by $205 billion in 2022, shrank the college wage premium by 2.1 percentage points, and modestly steepened the cross-sectional age-wage profile.